2020
DOI: 10.1051/e3sconf/202017508004
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the use of protein-carbohydrate complex based on mung bean seeds in the functional meat products technology

Abstract: The use of new non-traditional types of plant materials in the diet is one of the ways to improve the meat products’ quality. The combination of plant proteins with animals creates biologically active amino-acid complexes which increase its bioavailability for organism and biological value of the product. In this case, the use of non-traditional plant materials in the production technology of new types of sausage products to improve the quality of the end product is prospective and relevant. Research objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…One of the major anticipated demands for this crop in the future is related to its high-protein content, leading to the potential for meat replacement products (Alexeev, Alexeeva, Enaleva, Tupolskikh, & Shumskaia, 2020). In addition to providing a valuable source of protein, mungbean also contains high levels of antioxidant and phenolic compounds (Ganesan & Xu, 2018;Hou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major anticipated demands for this crop in the future is related to its high-protein content, leading to the potential for meat replacement products (Alexeev, Alexeeva, Enaleva, Tupolskikh, & Shumskaia, 2020). In addition to providing a valuable source of protein, mungbean also contains high levels of antioxidant and phenolic compounds (Ganesan & Xu, 2018;Hou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2019) found that including 20% and 30% texturised soy protein led to a notable decrease in overall acceptability compared to control meatballs. Other authors observed that adding soy and GMF created a distinct beany taste in meat products and decreased acceptance scores (Das et al ., 2008; Alexeev et al ., 2020). Yuliarti et al .…”
Section: Resultsmentioning
confidence: 99%
“…Despite its promising potential, only a few studies have explored the use of GMF as a meat substitute. Alexeev et al (2020) used GMF to replace minced beef in sausages, increasing protein content and improving moisture retention thanks to the water-binding capacity of GMF's carbohydrates. The product's flavour and taste remained largely unchanged when the substitution ratio was less than 15%.…”
Section: Introductionmentioning
confidence: 99%
“…In the technology of meat semi-finished products with additives of plant and animal origin, which are proteincarbohydrate complexes, an important role is played by the water-binding capacity, moisture-retaining capacity and fat-retaining capacity of minced meat [17]. Table 2 presents the results of determining the WBC, MRC and FRC of the control and experimental samples of minced meat.…”
Section: Resultsmentioning
confidence: 99%